2020
DOI: 10.1186/s12893-020-00824-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open surgery for pheochromocytoma: a meta-analysis

Abstract: Background: Surgical resection is the main treatment for pheochromocytoma (PHEO). Although open surgery (OS) has been shown to be safe and feasible, the safety and efficacy of laparoscopic surgery (LS) for PHEO remain controversial due to the uncertain effects of pneumoperitoneum on haemodynamics and the complexity of the tumour itself. This study was performed to compare the treatment outcomes of OS with those of LS for patients with PHEO. Methods: A systematic search through November 11, 2019, was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
3
21
0
1
Order By: Relevance
“…Genetic information was available in 136 patients, of whom 29.4% had a predisposing hereditary syndrome (the most common MEN2A). 162 surgeries were included (3 patients underwent adrenalectomy twice), laparoscopic adrenalectomy in 156 patients (bilateral in 12), open adrenalectomy in 14 (bilateral in 2 patients). After a median follow-up of 41.2 months, 6 patients died, but only one death was attributable to the pheochromocytoma (progression of metastatic disease).…”
Section: General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic information was available in 136 patients, of whom 29.4% had a predisposing hereditary syndrome (the most common MEN2A). 162 surgeries were included (3 patients underwent adrenalectomy twice), laparoscopic adrenalectomy in 156 patients (bilateral in 12), open adrenalectomy in 14 (bilateral in 2 patients). After a median follow-up of 41.2 months, 6 patients died, but only one death was attributable to the pheochromocytoma (progression of metastatic disease).…”
Section: General Characteristicsmentioning
confidence: 99%
“…risk factors for postsurgical complications included diabetes [4], tumour size [11], preoperative total urinary metanephrine excretion [7], preoperative systolic blood pressure [7] and open adrenalectomy [12], among others.…”
mentioning
confidence: 99%
“…A catecholamine crisis can also lead to heart failure, pulmonary edema, arrhythmias, and intracranial haemorrhage. 6 When we suspect pheochromocytoma, additional examination such as urine or plasma metanephrine levels and imaging studies such as computed tomography (CT) scan and magnetic resonance imaging (MRI) are needed.…”
Section: General Clinical Presentation and Principal Managementmentioning
confidence: 99%
“…1 Minimal invasive techniques (laparoscopy or retroperitoneoscopy) have become the standard approach to pheochromocytoma surgery due to fewer complications and faster healing than open surgery. 6 Compared to open surgery, minimal invasive techniques only need a small incision, which is related to better cosmetic results. 6…”
Section: General Clinical Presentation and Principal Managementmentioning
confidence: 99%
“…Since the 1990s, laparoscopic techniques have emerged as an alternative to open surgical approaches ( 5 ). Two recent meta-analyses have confirmed that laparoscopic adrenalectomy (LA) is associated with lower volume of bleeding, lower intraoperative hemodynamic instability (IHD) and better postoperative recovery when used in the treatment of PHEO ( 6 , 7 ). However, because of the limited movement range of the instrument, physiological tremor magnification, and unclear two-dimensional images, it has been suggested that the risk of surgery is increased, especially for large PHEOs ( 8 ).…”
Section: Introductionmentioning
confidence: 99%